Negligible contribution of adaptation of ocular opponency neurons to the effect of short-term monocular deprivation - Wang, Jue; Song, Fangxing; He, Xin; Bao, Min (Frontiers in Psychology, 2024)
Modeling work on binocular rivalry has described how ocular opponency neurons represent interocular conflict. These neurons have recently been considered to mediate an ocular dominance shift to the eye that has viewed a backward movie for long during which time the other eye is presented with a regular movie. Unlike typical short-term monocular deprivation, the visual inputs are comparable across eyes in that "dichopticbackward-movie" paradigm. Therefore, it remains unclear whether the ocular opponency neurons are also responsible for the short-term monocular deprivation effect which is prevalently explained by the homeostatic compensation theory. We designed two experiments from distinct perspectives to investigate this question. In Experiment 1, we mitigated the imbalance in the activity of opponency neurons between the two eyes during monocular deprivation by presenting video stimuli alternately. In Experiment 2, we directly evaluated the response of opponency neurons before and after monocular deprivation using SSVEP techniques. However, consistent with each other, both experiments failed to provide reliable evidence supporting the involvement of ocular opponency neurons in the short-term monocular deprivation effect. Therefore, our results suggest that ocular opponency neurons may not play an essential role in the short-term monocular deprivation effect, potentially due to interference from the homeostatic plasticity mechanism.